THE ROLE AND MUTUAL INTEGRATION OF CAD, CAE, AND CAM SYSTEMS IN MECHANICAL ENGINEERING - Yo’ldashev Bilolxon Iqboljon o’g’li, (Ta'lim innovatsiyasi va integratsiyasi, 2026)
Abstract:  The  contemporary  development  of  mechanical  engineering  is inseparable  from  the  progressive  convergence  of  Computer-Aided  Design  (CAD), Computer-Aided  Engineering  (CAE),  and  Computer-Aided  Manufacturing  (CAM) into a unified digital environment capable of supporting the full product lifecycle from concept  generation  to  production  planning,  machining,  inspection,  and  subsequent optimization. The scientific and practical relevance of this topic lies in the fact that traditional  drawing-based  and  document-fragmented  workflows  no  longer  provide adequate speed, traceability, or accuracy for modern manufacturing systems that must operate  under  conditions  of  mass  customization,  compressed  development  cycles, rising quality  expectations,  and increasing  integration  between  physical  and  digital production  assets.  In  a  model-based  enterprise,  digital  models  are  not  passive geometric representations but authoritative information carriers that connect design intent,  simulation  data,  process  planning,  manufacturing  semantics,  and  quality assurance.  This  article  analyzes  the  role  of  CAD,  CAE,  and  CAM  systems  in mechanical engineering and examines the  mechanisms, benefits, and constraints of their integration within contemporary product realization environments. The study is based  on  a  structured  analytical  review  of  standards  documents,  NIST  technical publications, and recent scholarly literature on model-based definition, digital thread architectures, CAD-to-CAE interoperability, feature recognition, process knowledge representation,  and  digital  twin  applications  in  machining.  The  results  show  that effective  CAD–CAE–CAM  integration  improves  consistency  of  engineering  data, reduces  design-to-manufacturing  cycle  time,  strengthens  product  quality,  enables earlier  manufacturability  assessment,  supports  more  reliable  process  planning,  and provides the informational backbone for digital thread and digital twin implementation. At  the  same  time,  the  review  reveals  persistent  obstacles, including  semantic  gaps between  design  and  manufacturing  representations,  incomplete  interoperability, standards  implementation  costs,  skills  shortages,  fragmented  knowledge  structures, and the continuing coexistence of model-based and drawing-based workflows. It is concluded that the most productive direction for mechanical engineering enterprises is not  the isolated improvement  of  CAD,  CAE, or  CAM  modules  separately, but  the establishment  of  model-centric,  standards-based,  and  semantically  rich  integration architectures in which a single authoritative product definition can be reused across design,  analysis,  planning,  machining,  inspection,  and  lifecycle  feedback.  The scientific novelty of the article lies in presenting CAD, CAE, and CAM not as separate software  categories,  but  as  functionally  interdependent  layers  of  a  unified  digital manufacturing logic whose maturity increasingly depends on standards such as STEP AP242, model-based definition, manufacturing feature semantics, and digital thread continuity.  The  practical  significance  of  the  article  lies  in  identifying  a  realistic framework for universities, industrial enterprises, and engineering teams seeking to improve mechanical product development efficiency through deeper CAx integration.